2021
DOI: 10.1186/s12906-021-03400-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nanomicelle curcumin capsules on prevention and treatment of oral mucosits in patients under chemotherapy with or without head and neck radiotherapy: a randomized clinical trial

Abstract: Background One of the most prevalent complications of chemotherapy and radiotherapy is oral mucositis (OM) and manifests as erythema and ulceration. Curcumin is one of the components of turmeric and possesses anti-inflammatory and anti-oxidative features. Some of studies have proved the effectiveness of Curcumin in OM. This study aimed to investigate the effects of nanomicelle Curcumin on OM related chemotherapy and head and neck radiotherapy. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 31 publications
(35 reference statements)
0
37
0
Order By: Relevance
“…Five hundred and five studies that did not fulfill the eligibility criteria were excluded. In total, nineteen studies [ 24 , 35 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ] were included and processed for data extraction ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five hundred and five studies that did not fulfill the eligibility criteria were excluded. In total, nineteen studies [ 24 , 35 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ] were included and processed for data extraction ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen RCTs were included [ 24 , 35 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. The number of participants ranged between 11 and 178 individuals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All patients received 80 mg of curcumin nanomicelle capsules twice a day for 7 weeks. The results showed that in patients who were under chemotherapy and head and neck radiotherapy, curcumin administration managed to significantly decrease the OM severity [ 72 ]. Similar results were presented by Charantinath et al who evaluated the efficacy and safety of a curcumin gel in the alleviation of OM in cancer patients undergoing radiochemotherapy [ 73 ].…”
Section: Radioprotection By Curcuminmentioning
confidence: 99%